Metamagnetic transition and meta-stable magnetic state in Co-doped Fe3GaTe2 - Ahn, Hyo-Bin; Lim, Hyunjong; Song, Jaegu; Lee, Jisung; Park, Seung-Young; Joe, Minwoong; Kang, Chang-Jong; Kim, Kyoung-Whan; Park, Tae-Eon; Park, Tuson; Lee, Changgu (Royal Society of Chemistry, 2024)
The transition between the ferromagnetic (FM) and anti-ferromagnetic (AFM) phases in van der Waals (vdW) magnets has been extensively studied since the discovery of vdW magnets, due to the importance of both transitions within a single material. Recently, among vdW magnets, Fe3GaTe2 (FGaT) has garnered significant attention for its robust FM properties that remain stable above room temperature. Also, the FM to AFM phase transition in this material has been achieved through substitutional Co-atom doping at Fe sites. Here, we have reconfirmed the FM to AFM phase transition in FGaT and observed the metamagnetic transition between the two magnetic phases. Furthermore, the meta-stable magnetic state in 19-22% Co-doped FGaT in a certain field range was noted, which vanishes when the doping level increases further. Interestingly, when measuring the minor loop during the phase transition, its magnetization under a field-sweep reversing field is maintained in a meta-stable magnetic state region. The persistence of magnetization, which indicates the co-existence of AFM and FM domains in this meta-stable magnetic region, creates multi-level configurations that enable advanced applications in multi-level logic devices, neuromorphic computing, and applications involving magnetic domains. Our findings can expand the application scope and the utilization methods of vdW magnets.